Applying match statistics to increase serving performance - Barnett, T.; Meyer, D.; Pollard, G. (Medicine and Science in Tennis, 2008)
A large database of tennis statistics is used to calculate player match statistics for each court surface. Analysis is carried out to determine serving strategies to increase performance. The results of the analysis could be used by players and coaches to possibly increase serving performance. There is a range of published material on the use of match statistics/probabilities to increase serving performance. Gale1 used a simple mathematical model to determine an optimal strategy for serving in tennis. Norman2 used dynamic programming to determine an optimal strategy of whether to use a slow or fast serve on the first and second serve. George3 used a simple probabilistic model to determine a serving strategy in tennis and stated that the usual serving strategy may not be optimal. Professional tennis matches were used as examples to support the claim. Gillman4 developed a similar analysis to serving strategies. Hannan5 also analysed different serving strategies, with the added complexity of the opponent returning the serve in such a way that the server countered with a strong shot or was forced to hit a weak shot. Pollard6 determined a method for finding the optimal risks that should be taken by the server on the first and second serves.